Design and optimization of novel dehumidification strategies based on modified nucleation model in three-dimensional cascade. (15th November 2019) - Zhang, Guojie; Zhang, Xinzhe; Wang, Fangfang; Wang, Dingbiao; Jin, Zunlong; Zhou, Zhongning
Abstract: To decrease the wetness loss and increase the efficiency in nuclear plant steam turbine, several novel dehumidification strategies are presented in this paper and the dehumidification effect is tested. The modified nucleation model is built firstly, and the accuracy of the modified nucleation model combined with several droplet growth models is investigated and discussed. Secondly, the non-equilibrium condensation (NQC) characteristics in Dykas cascade are studied, the relationship among the parameters is obtained. Secondly, five novel dehumidification strategies are presented, and the dehumidification effect is evaluated. With the passage layer increasing, the ability of the wetness loss reduction is gradually enhanced. When the passage layer increases to 5, the wetness loss is reduced to 1.15 kJ/kg, but which is at the cost of reducing the blade strength. And the LNB_LNE_LWC is the best choice by balancing the dehumidification effect and the blade strength, succeeding in reducing the wetness loss to 1.42 kJ/kg. At last, the NQC characteristics in three-dimensional cascade are investigated numerically, the structure dehumidification effect with different passage layers is evaluated in detail. The results in this paper can give a scientific basis and reference for the design and optimization of the dehumidification strategy in nuclear plant steam turbine. Graphical abstract: Image 1 Highlights: The modified nucleation model is built. Five novel dehumidification structures are presented. The LNB_LNE_LWC is the best choice by considering all factors. The stage wetness loss is reduced to 2.22 kJ/kg when the passage layer reaches 9.